QUALITY OF LIFE IN PATIENTS AFTER KNOWN METHODS OF ANTI-REFLUX SURGERY OF HIATAL HERNIAS - Babii, O.M.; Prolom, N.V.; Shevchenko, B.F.; Tarabarov, S.O.; Polyak, N.V.; Zeleniuk, O.V.; Mylostуva D.F. (World of Medicine and Biology, 2023)
To assess the quality of life, a retrospective study of the effectiveness of well-known methods of antireflux operations (Nissen, Toupet, Dor) was performed in 131 patients with hiatal hernias during a follow-up period of 2 to 4 years. According to the GERD-HRQL questionnaire, 21.6 % were dissatisfied with the Nissen fundoplication, Toupet – 19.0 %, and Dor – 15.0 %. According to MOS SF-36, patients’ quality of life was worse after Nissen fundoplication (p